A CRITICAL ASSESSMENT OF SKILLS AND KNOWLEDGE FOR ENTRY-LEVEL MARKETING JOBS: A DELPHI STUDY. Issue 4 (2nd October 2019) - Yeoh, Poh-Lin
Abstract : While the marketing education literature has contributed to our understanding of the skills that are important for successful employability, there has been limited effort to study both technical and non-technical skills together and second, their relative importance. This study addresses these gaps by conducting a Delphi study with a panel comprising of 12 human resource managers and 15 marketing managers. Among the list of 51 skills identified, the panelists selected and ranked 20 skills as being the most critical for entry-level marketing graduates. We further compared our results with four different industry studies and discuss their implications for marketing education.